2019
DOI: 10.1021/acs.energyfuels.9b01436
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Emission Characteristics of Ammonium Sulfate Aerosols in Flue Gas Downstream of Selective Catalytic Reduction

Abstract: Selective catalytic reduction (SCR) technology has been widely employed in coal-fired power plants (CFPPs) because of its high efficiency in NO x removal. Ammonium sulfate aerosols are the byproducts of the SCR of NO x with NH3, which lead to adverse effects such as air preheater blockage and increased particulate matter emissions. In this study, the formation mechanism and emission characteristics of ammonium sulfate aerosols in the simulated SCR flue gas were investigated by thermodynamic calculations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Theoretically, the area of the two hydrogen-consuming peaks shall be basically the same, however, it was found that the area of the second peak was larger than that of the first peak due to the reason that the bivalent state {Cu 2+ -O 2− -Cu 2+ } 2+ was thermally unstable [38]. Pretreatment of samples at 500 • C for 4 h in Ar atmosphere before hydrogen temperature programmed reduction will make {Cu 2+ -O 2− -Cu 2+ } 2+ desorption O 2 , leading to high temperature self-reduction of this species and conversion of a monovalent {Cu + --Cu + } 2+ ,as shown in Equation (5). According to this feature, {Cu 2+ -O 2− -Cu 2+ } 2+ had reduced to a monovalent {Cu + --Cu + } 2+ without consuming hydrogen in the heating pretreatment stage before the temperature programmed reduction with hydrogen.…”
Section: H 2 -Tprmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the area of the two hydrogen-consuming peaks shall be basically the same, however, it was found that the area of the second peak was larger than that of the first peak due to the reason that the bivalent state {Cu 2+ -O 2− -Cu 2+ } 2+ was thermally unstable [38]. Pretreatment of samples at 500 • C for 4 h in Ar atmosphere before hydrogen temperature programmed reduction will make {Cu 2+ -O 2− -Cu 2+ } 2+ desorption O 2 , leading to high temperature self-reduction of this species and conversion of a monovalent {Cu + --Cu + } 2+ ,as shown in Equation (5). According to this feature, {Cu 2+ -O 2− -Cu 2+ } 2+ had reduced to a monovalent {Cu + --Cu + } 2+ without consuming hydrogen in the heating pretreatment stage before the temperature programmed reduction with hydrogen.…”
Section: H 2 -Tprmentioning
confidence: 99%
“…In addition to affecting the natural environment, NO also causes respiratory, cardiovascular, and cerebrovascular diseases [1,2]. Although most coal-fired power station boilers are equipped with a Selective Catalytic Reduction (SCR) denitration system [3], ammonia escapes, the narrow temperature window, the highly toxic of V 2 O 5 catalyst, and the blocked downstream air preheater caused by side reactions seriously affects the stability and reliability of SCR [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…We conjecture this is caused by the co-occurrence of their propensity for the air-water interface as well as the strong NH 4 + -OH interaction, which brings OH closer to dodecyl OS. Na + and NH 4 + , both being atmospherically abundant cations respectively originated from marine and anthropogenic sources, [99][100][101] exhibit different air-water interface propensities and interactions with OH, eventually resulting in distinct effects on reactivity alteration of dodecyl OS. Despite the phenomenon being special to the investigated combination of species, future studies of atmospheric fates of organic compounds, especially surface-active compounds, may require careful consideration in the effect by their counterions as well as other unexplored factors, which altogether potentially affect the interpretation of experimental kinetics outcome.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…However, mercury oxidation ability of MnO 2 /TiO 2 was significantly restrained in the presence of SO 2 , and more than 80% of Hg 0 escaped [20]. The optimal temperature of the Mn-based catalyst for mercury oxidation was always lower than 250 • C, and the formation of NH 4 HSO 4 was the main reason for the catalyst deactivation at low temperature [23]. One way to enhance mercury oxidation ability was to add various auxiliary metal components into the Mn-based catalyst and keep low-temperature activity.…”
Section: Introductionmentioning
confidence: 96%